Nanostructured Anodic Oxide Films of Niobium: Features of Electrochemical Formation, Functional Properties and Applications (Review) - Вayrachniy B. I.; Tokareva, I. A. (Physics and Chemistry of Solid State, 2016)
The review summarizes data on the anodic behavior of niobium in aqueous solutions. Features of electrochemical formation nanostructured oxide coatings on niobium by anodic oxidation are systematized. The article deals with theoretical aspects formation of the porous anodic oxide layers. The influence of process parameters and the characteristics of the electrolyte on layer of niobium oxide were analyzed. The functional properties of porous coating on niobium are considered and promising areas of practical application identified.